Long-Term Effects of Oxymetholone vs. Testosterone with orWithout ZnSO4 on Growth Performance of Turkey Chicks - Arshami, J.; Heydar-Poor, M.; Zarghi, H.; Pilevar, M.; Esmailzadeh, M. (International Journal of Poultry Science, 2009)
Oxymetholone at 0.6 mg/kg feed or mixed with ZnSO4 (45mg/kg feed), testosterone at 10 mg/kg feed or mixed with ZnSO4 (45 mg/kg feed) and 0 mg/kg of either one were given to 180 turkey chicks (n = 9; r = 4) from 6-18 weeks of age to determine their effects on growth performance. Body Weight (BW) was increased gradually in all treatments when compared to the control group with the highest level for oxymetholone and testosterone alone respectively. Feed Intake (FI) during 12 weeks of study decline slightly in all treatments with the lowest level for oxymetholone + ZnSO4 and the highest level for control group. Feed Conversion Ratio (FCR) at the end of study was 4.77 for control group and 4.15, 4.32, 4.50 and 4.69 for different treatments, respectively. Growth Rate (GR) differed for each week and treatment. Overall, the treatment groups showed higher GR when compared to control group in every week. The percentage of Carcass Weight (%CW) was increased significantly (p